Tema â€œKeluargaâ€ dan Relevansinya dalam Pembelajaran Bahasa Jerman - S, Sri Santia; Anwar, Muh. (Interference: Journal of Language, Literature, and Linguistics, 2021)
This study aims to obtain data on the theme of "family" and its relevance in learning German for class XII IIS SMA Negeri 11 Makassar. This research is a qualitative descriptive study. The population of this study were all students of class XII SMA Negeri 11 Makassar who studied German which consisted of 3 (three) classes, namely class XII IIS 1, XII IIS 2 and XII IIS 3 with a total of 106 people. The sample technique used was purposive sampling, amounting to 36 students. The data collection technique used an open questionnaire. The data that has been obtained were analyzed descriptively qualitatively. The results showed that family life in Germany was very good. This can be seen based on the culture of life through the attitude of independence, equal rights (work) in the family, and free time. The relevance of learning in this study is mainly on cultural themes that themes like this are suitable themes to be studied because the purpose of language learning is not only to mastery of language but also to culture, namely by looking for learning materials that are related to cultural and universal themes. but on the one hand it is specific in purpose so that the learning process occurs much faster because the themes used or studied also exist in our culture. In addition, we see that the German family is very punctual and disciplined, so its relevance in the learning process is highly respected by the nature of discipline and timeliness.